The effect of CO2 on the speciation of RbBr in solution at temperatures to 579 degrees C and pressures to 0.26 GPa - Evans, Katy; Gordon, R.; Mavrogenes, J.; Tailby, N. (Pergamon-Elsevier Science Ltd, 2009)
Carbon dioxide- and salt-bearing solutions are common in granulite, ore-forming and magmatic environments. The presence of CO2 affects mineral solubilities, fluid miscibility, and viscosity and wetting properties, and is expected to affect salt speciation. EXAFS measurements of RbBr-H2O-CO2 fluids contained in corundum-hosted synthetic fluid inclusions (SFLINCs) have been used to investigate the effect of CO2 on salt speciation at temperatures to 579 degrees C and pressures to around 0.26 GPa. Forward modelling indicates that solute dehydration is difficult to distinguish from up to around 40% of Rb-Br ion-pairing, so results refer to the total number of nearest neighbours, which are likely to be mostly O present in waters of hydration, but may also include Br, if ion pairing is present. Additionally, results relate to the number of well-ordered neighbours in the first shell, because nearest neighbours with a high degree of disorder may be present but contribute minimally to the EXAFS signal. Analysis of the EXAFS results at the Rb edge for the CO2-free solution is consistent with previous work and shows that the number of nearest neighbours for Rb in CO2-free solutions decreases from 6 plus/minus 0.6 to 1.4 plus/minus 0.1 as temperature increases from 20 degrees C to 534 degrees C. The decrease is accompanied by a decrease in Rb-x bondlengths of 0.05 Angstroms, where x is the first shell scatterer. Results for the CO2-bearing solution are different to those for the CO2-free solution. The number of nearest neighbours is 16 and 22% less than for the CO2-bearing solution at 312 and 445 degrees C respectively. Changes in the numbers of nearest neighbours correlate well with calculated changes in the bulk solution dielectric constant; CO2-bearing and CO2-free solutions lie on the same trend, which suggests that it may be possible to calculate the number of nearest neighbours from dielectric constant. Rb-x bondlengths for the CO2-bearing solution are statistically indistinguishable to those for the CO2-free inclusions. Results for Br are worse quality than for Rb so EXAFS analysis could not be completed, however XANES spectra for CO2-free and CO2-bearing solutions are consistent with solute dehydration similar to that recorded by the Rb spectra. The conclusions of this study provide support for the notion that CO2 has a fundamental effect on the mechanics of solubility, and that these effects should be incorporated into conceptual and quantitative thermodynamic models.uids contained in corundum-hosted synthetic uid inclusions (SFLINCs) have been used to investigate the eect of CO2 on salt speciation at temperatures to 579C and pressures to around 0.26 GPa. Forward modelling indicates that solute dehydration is dicult to distinguish from up to around 40% of Rb-Br ion-pairing, so results refer to the total number of nearest neighbours, which are likely to be mostly O present in waters of hydration, but may also include Br, if ion pairing is present. Additionally, results relate to the number of well-ordered neighbours in the first shell, because nearest neighbours with a high degree of disorder may be present but contribute minimally to the EXAFS signal. Analysis of the EXAFS results at the Rb edge for the CO2-free solution is consistent with previous work and shows that the number of nearest neighbours for Rb in CO2-free solutions decreases from 6 0.6 to 1.4 0.1 as temperature increases from 20C to 534C. The decrease is accompanied by a decrease i Rb-x bondlengths of 0.05 A, where x is the rst shell scatterer. Results for the CO2-bearing solution are dierent to those for the CO2-free solution. The number of nearest neighbours is 16 and 22% less than for the CO2-bearing solution at 312 and 445C respectively. Changes in the numbers of nearest neighbours correlate well with calculated changes in the bulk solution dielectric constant; CO2-bearing and CO2-free solutions lie on the same trend, which suggests that it may be possible to calculate the number of nearest neighbours from dielectric constant. Rb-x bondlengths for the CO2-bearing solution are statistically indistinguishable to those for the CO2-free inclusions. Results for Br are worse quality than for Rb so EXAFS analysis could not be completed, however XANES spectra for CO2-free and CO2-bearing solutions are consistent with solute dehydration similar to that recorded by the Rb spectra. The conclusions of this study provide support for the notion that CO2 has a fundamental eect on the mechanics of solubility, and that these eects should be incorporated into conceptual and quantitative thermodynamic models.